Levels, Distribution and Risk Assessment of Polycyclic Aromatic Hydrocarbons in Varieties of Cereal in Yobe State, Nigeria - Joseph Akan (Journal of Chemistry Letters)
Cereal (corn, guinea corn and millet) samples from Bade and Karasuwa Local Government Area, Yobe State, Nigeria were collected for analysis of PAHs using GC/MS. The highest total mean concentration value of PAHs (1.56E-06 mg/kg) was observed in corn from Mashayan Bululu agricultural location, while millet from Wachakal Ngurodi agricultural location shows the lowest total concentration value of 7.93E-10 mg/kg. The levels of all the sixteen PAHs in the cereal samples were below the maximum allowable concentrations (MACs). Data obtained from cancer risk assessment in cereal samples were below the regulatory standard cancer risk values of 10-5. The highest average daily dose values in cereals from all the six agricultural locations were recorded in guinea corn from Mashayan Bululu agricultural location, while the lowest average daily dose values were observed in millet from Wachakal Ngurodi agricultural location in Bade and Karasuwa Local Govenrment areas respectively. The non-carcinogenic PAHs through the consumption of corn, guinea corn and millet from the study agricultural locations produced hazard quotient and hazard index of less than 1, which is the level described by USEPA as having no appreciable risk for the development of non-cancer health effects. Results from ILCRs was less than 10−4 and shows no health risk for now. However, continuous monitoring of PAHs in the cereals is necessary to identify the fate of PAHs and their effects on the residents that depends on these cereals as food.